Personality disclosure on social network sites: An empirical examination of differences in Facebook usage behavior, profile contents and privacy settings. (November 2017) - Tsai, Tsai-Hsuan; Chang, Hsien-Tsung; Chang, Ya-Ching; Chang, Yung-Sheng
Abstract: The purpose of this study was to objectively investigate the usage patterns of Facebook users with different personalities based on the Big Five model of personality traits and to observe whether their social behaviors on Facebook reflect their offline personalities. In addition, subjects with high and low degrees of each personality trait were investigated to see whether they had different Facebook usage patterns. A total of 111 university students participated in the study. The experiment was divided into two phases: Phase I included a personality test based on the Big Five Inventory, and Phase II consisted of two months of data collection. The results showed that those with high agreeableness were well-socialized on Facebook and that those with high conscientiousness managed a higher number of groups. The users with high openness to experience had more friends and photos on Facebook and were more inclined to post text and make comments. These findings confirmed those of previous studies, showing that extraverts had more friends on Facebook and were more likely to use functions such as messages and wall posting. In contrast to previous studies, the results found that users with low emotional stability were associated with higher levels of event participation, family and relative edits and blocked apps than those with high emotional stability. Regarding privacy, Facebook was used as a platform though which extroversive people could interact with their real-life friends, and they were less interested in using Facebook to interact with strangers on the Internet. Highlights: This study objectively investigated the usage patterns of Facebook users with different personalities. This study objectively observed whether users' social behaviors on the site reflect their offline personalities. A Facebook app - the graph application programming interface (API) - was used to acquire the subjects' usage behavior data. The collected data consisted of profile content, usage behavior and privacy settings. This study generated new results, such as those for the agreeableness and emotional stability traits.